UJI ORGANOLEPTIK SOSIS DAGING AYAM DENGAN PENAMBAHAN DAUN KELOR - Luciana Sari; Agustina Widyasworo; Dhenok Wahyu Lestari (AVES: Jurnal Ilmu Peternakan, 2019)
The purpose of this study was to determine the organoleptic test of chicken sausage with the addition of Moringa leaves. This research was conducted at the Laboratory of Animal Husbandry, Department of Animal Husbandry of Balitar Islamic University, Blitar, in July 2019. The use of Moringa leaf flour concentration in the study was 0%, 2%, 4%, and 6%, using the Completely Randomized Design (CRD) method consisting of 4 treatments 6 repetitions. The results of this study are that there are very significant differences in color, aroma, taste and texture so that it can be concluded that the addition of Moringa leaf flour has a significant effect on the organoleptic test of chicken sausage with the addition of Moringa leaf flour.